CHANGING DEMOGRAPHIC PROCESSES: TRENDS, CHALLENGES AND PROSPECTS - Vositjon Imomov (International Scientific and Current Research Conferences, 2021)
This article analyzes the demographic situation and examines changes in population growth rates. At the same time, the factors influencing the birth and death rates and the trend of migration processes are clearly indicated. Based on the results of the analysis, forecasts of changes in demographic indicators and population growth are given.